2003
DOI: 10.1017/s0030605303000097
|View full text |Cite
|
Sign up to set email alerts
|

The Asian Tapir in Kerinci Seblat National Park, Sumatra: evidence collected through photo-trapping

Abstract: Kerinci Seblat National Park (KSNP) is the often photo-trapped in pairs. Repeat 'recapture' of the same individuals suggests that these pairings may be of largest protected area in which Asian tapir Tapirus indicus occurs. Data collected during 3 years of bio-long duration. Evidence of distribution and threats throughout the Park and adjacent forests was collected diversity surveys indicated that KSNP is one of the most important remaining areas for Asian tapir. Evidence of to produce a greater understanding o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
1
5

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(62 citation statements)
references
References 3 publications
1
55
1
5
Order By: Relevance
“…This pattern has already been reported in studies of lowland tapirs (Maffei et al 2002;Gó mez et al 2005), as well as with other species of the same genus (Williams 1984;Foerster 1998;Lizcano and Cavelier 2000;Holden et al 2003). Our results do not corroborate the idea that the tapir has cathemeral activity, which is characteristic of various selective grazing ungulates (van Schaik and Griffiths 1996).…”
Section: Circadian Activity Patternscontrasting
confidence: 64%
“…This pattern has already been reported in studies of lowland tapirs (Maffei et al 2002;Gó mez et al 2005), as well as with other species of the same genus (Williams 1984;Foerster 1998;Lizcano and Cavelier 2000;Holden et al 2003). Our results do not corroborate the idea that the tapir has cathemeral activity, which is characteristic of various selective grazing ungulates (van Schaik and Griffiths 1996).…”
Section: Circadian Activity Patternscontrasting
confidence: 64%
“…To date, evidence of interactions between tiger and tapir is limited to photographic records of tiger attacks on tapir and speculation over the tapir's status as a prey species (Lynam, 1999;Holden, Yanuar & Martyr, 2003). Even though the tapir was frequently photographed and along trails used by tiger, our analysis found only a low level of temporal overlap; tapir was predominantly nocturnal.…”
Section: Sumatran Tiger-prey Interactionmentioning
confidence: 49%
“…The result is almost similar to report by Novarino [4] which found that tapir was active most from 1800 hours to 0400 hours. Other than that, Holden et al [12] found that tapir was active mostly from 1800 hours to 0800 hours. Based on those studies, it is concluded that T. indicus starts its daily activity at 1800 hours and ends at between 0400 and 0800 hours.…”
Section: Species Composition and Ecology Of Selected Speciesmentioning
confidence: 99%